Parkinsonian Rest Tremor Is Associated With Modulations of Subthalamic High‐Frequency Oscillations. Issue 10 (6th October 2016) - Hirschmann, Jan; Butz, Markus; Hartmann, Christian J.; Hoogenboom, Nienke; Özkurt, Tolga E.; Vesper, Jan; Wojtecki, Lars; Schnitzler, Alfons
ABSTRACT: Background: High frequency oscillations (>200 Hz) have been observed in the basal ganglia of PD patients and were shown to be modulated by the administration of levodopa and voluntary movement. Objective: The objective of this study was to test whether the power of high‐frequency oscillations in the STN is associated with spontaneous manifestation of parkinsonian rest tremor. Methods: The electromyogram of both forearms and local field potentials from the STN were recorded in 11 PD patients (10 men, age 58 [9.4] years, disease duration 9.2 [6.3] years). Patients were recorded at rest and while performing repetitive hand movements before and after levodopa intake. High‐frequency oscillation power was compared across epochs containing rest tremor, tremor‐free rest, or voluntary movement and related to the tremor cycle. Results: We observed prominent slow (200‐300 Hz) and fast (300‐400 Hz) high‐frequency oscillations. The ratio between slow and fast high‐frequency oscillation power increased when tremor became manifest. This increase was consistent across nuclei (94%) and occurred in medication ON and OFF. The ratio outperformed other potential markers of tremor, such as power at individual tremor frequency, beta power, or low gamma power. For voluntary movement, we did not observe a significant difference when compared with rest or rest tremor. Finally, rhythmic modulations of high‐frequency oscillation power occurred within the tremor cycle. Conclusions: Subthalamic high‐frequency oscillation power is closely linked to the occurrence of parkinsonian rest tremor. The balance between slow and fast high‐frequency oscillation power combines information on motor and medication state. © 2016 International Parkinson and Movement Disorder Society